2020
DOI: 10.1016/j.radi.2019.11.094
|View full text |Cite
|
Sign up to set email alerts
|

Can the anode heel effect be used to optimise radiation dose and image quality for AP pelvis radiography?

Abstract: A study was conducted to determine whether the anode heel effect can be used to influence optimisation of radiation dose and image quality (IQ) for AP pelvis radiography. Methods:ATOM dosimetry phantom and an anthropomorphic phantom were positioned for AP pelvis. Using a CR system, images were acquired and doses were measured with phantom feet toward anode and then feet toward cathode. Exposure factors (kVp, mAs and SID) were systematically generated using a factorial design. Images were scored visually for qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, there were limited previous works quantifying the influence of anode heel effect on image quality in digital radiographs [ 16 ]. Previous studies demonstrated that the heel effect significantly impacted the signal-to-noise ratio (SNR) using an anthropomorphic phantom, but the image quality was not significantly different between pelvic radiographs with the head towards the anode and cathode directions [ 17 , 18 ]. Moreover, some previous studies performed post-processing heel effect correction (HEC) to minimize the inhomogeneous intensity in radiographs [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there were limited previous works quantifying the influence of anode heel effect on image quality in digital radiographs [ 16 ]. Previous studies demonstrated that the heel effect significantly impacted the signal-to-noise ratio (SNR) using an anthropomorphic phantom, but the image quality was not significantly different between pelvic radiographs with the head towards the anode and cathode directions [ 17 , 18 ]. Moreover, some previous studies performed post-processing heel effect correction (HEC) to minimize the inhomogeneous intensity in radiographs [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same thing was also expressed [4] who measured radiation doses, there was a significant difference in the dose to the testes between the anode in the distal part and the anode in the proximal part, while the anode was in the distal part and the anode in the proximal part, there was no significant difference for the ovaries.…”
Section: Contrast Calculationmentioning
confidence: 75%
“…The irradiation conditions for the supine and sitting positions were the same. The pelvic irradiation conditions were a tube voltage of 80 kV with 2.7 mm Al specific filtration, focus-detection surface distance of 120 cm, tube current-time product of 22 mAs, and irradiation field size of 43 × 35.4 cm 2 [22]. An x-ray tube, an x-ray source, a bed (height 60 cm, length 240 cm, width 120 cm), portable x-ray equipment, and a phantom simulating a patient were prepared in a virtual hospital room filled with air consisting of density 0.001293 (g cm −3 ), composition 14 N (79.6%), 15 N (0.4%), 16 O (20%).…”
Section: Simulation Of the Behaviour Of Scattered Radiation During Ho...mentioning
confidence: 99%